PERBANDINGAN PEMBERIAN SUSU FORMULA DAN ASI EKSKLUSIF TERHADAP STATUS GIZI BAYI USIA 6-12 BULAN DI PUSKESMAS GONDANGLEGI KABUPATEN MALANG: COMPARISON OF GIVING FORMULA MILK AND EXCLUSIVE BREAST MILK TO THE NUTRITIONAL STATUS OF BABIES AGED 6-12 MONTHS AT THE GONDANGLEGI COMMUNITY HEALTH CENTER MALANG REGENCY - Utami, Dian Asih Ning (WELL BEING, 2024)
Background: Nutrition is a fundamental issue in public health. One way of sustaining optimal growth and development can be maintained through providing sufficient breast milk. The aim of this study was to determine the comparison of the nutritional status of babies aged 6-12 months who were given formula milk and exclusive breast milk at the Gondanglegi Primary Health Centers Malang Regency. Subjects and Methods: This research method uses a quantitative cross sectional design approach. The research population was 152 babies aged 6-12 months and their mothers at the Gondanglegi Community Health Center, Malang Regency. The number of samples that met the sample criteria used the accidental sampling technique. Data were collected using a questionnaire to fill in the milk feeding history and record the results of measuring the baby's weight and body length on the observation sheet. Data analysis used the Wilcoxon test. Results: The results of the study showed that there was a significant comparison of the nutritional status of babies aged 6-12 months who were given exclusive breast milk and formula milk, with the results of the Wilcoxon analysis test showing p = 0.000 (p < 0.05). Conclusion: Information updates through activities need to be held by health service agencies either in live forums or online, such as outreach activities about the negative impact of giving formula milk on the nutritional status of babies.